Government to Citizens (G2C) communication and use of social media in the post-disaster reconstruction phase. (1st January 2018) - Tagliacozzo, Serena; Magni, Michele
ABSTRACT: Post-disaster reconstruction (PDR) poses specific and complex challenges that government agencies have to deal with. Existing crisis management and communication models as well as literature on social media adoption by public organisations tend to focus on the critical stage, neglecting the issues that arise when the social, physical and cultural environments affected by a disaster have to be rebuilt. Conversely, this paper presents some preliminary findings on the Government to Citizen (G2C) communications and social media usage in PDR settings. The PDR process that followed the earthquakes in Emilia-Romagna (Northern Italy) in 2012 was used as a case study. Data derived from field notes and multiple-choice questionnaires revealed that government agencies provided information mainly about housing and infrastructure and financing and that they addressed this information to all citizens, although information was sometimes targeted specifically to business people, homeowners and members of community-based groups. Government officers gave preference to face-to-face contacts, Web portals and printed material. Social media were used predominantly as additional means of communication of PDR-related information, thus underrating their potential for community engagement and G2C bidirectional communication. In the discussions, findings are integrated into and validated against literature and communication theories.